Humans and Dolphins: Decline and Fall of Adult Neurogenesis - Parolisi, Roberta; Cozzi, Bruno; Bonfanti, Luca (Frontiers in Neuroscience, 2018)
Pre-clinical research is carried out on animal models, mostly laboratory rodents, with the ultimate aim of translating the acquired knowledge to humans. In the last decades, adult neurogenesis has been intensively studied since it is viewed as a powerful tool for fostering brain plasticity and possibly repair. Yet, occurrence, location and rate of adult neurogenesis vary among mammals: the capability for constitutive neuronal production is substantially reduced when comparing small-brained, short living (e.g., laboratory rodents) and large-brained, long-living species (e.g., humans, dolphins). Several difficulties concerning scarce availability of fresh tissues, technical limits and ethical concerns did contribute in delaying and diverting the achievement of the picture of neurogenic plasticity in large-brained mammals. Some reports appeared in the last few years, starting to shed more light on this issue. Recent studies indicate that neurogenesis is vestigial, or possibly absent, in regions of the adult human brain where in rodents neuronal addition continues into adult life. Analyses carried out in dolphins, mammals devoid of olfaction, but descendant of ancestors provided with olfaction, has shown disappearance of neurogenesis in both neonatal and adult individuals. Heterogeneity in mammalian structural plasticity remains largely underestimated by scientists focusing their research in rodents. Comparative studies are the key to understand the function of adult neurogenesis and the possible translational significance of neuronal replacement in humans. Here, we summarize comparative studies on adult neurogenesis and discuss the evolutionary implications of variations on the recruitment of new neurons in different regions and different species.